Bacterial Transformation of Aromatic Monomers in Softwood Black Liquor - Navas, Laura E.; Dexter, Gara; Liu, Jie; Levy-Booth, David; Cho, MiJung; Jang, Soo-Kyeong; Mansfield, Shawn D.; Renneckar, Scott; Mohn, William W.; Eltis, Lindsay D. (Frontiers in Microbiology, 2021)
The valorization of lignin, a major component of plant-derived biomass, is essential to sustainable biorefining. We identified the major monoaromatic compounds present in black liquor, a lignin-rich stream generated in the kraft pulping process, and investigated their bacterial transformation. Among tested solvents, acetone extracted the greatest amount of monoaromatic compounds from a softwood black liquor, with guaiacol, vanillin, and acetovanillone, in an approximately 4:3:2 ratio, constituting ~90% of the total monoaromatic content. 4-Ethanol guaiacol (4EG), vanillate, and 4-propanol guaiacol were also present. Bacterial strains that grew on minimal media supplemented with the black liquor extracts at 1 mM total aromatic compounds included Pseudomonas putida KT2442, Sphingobium sp. SYK-6, and Rhodococcus rhodochrous EP4. By contrast, the extracts inhibited the growth of R. jostii RHA1 and R. opacus PD630, strains extensively studied for lignin valorization. Of the strains that grew on the extracts, only R. rhodochrous GD01 and GD02, isolated for their ability to grow on acetovanillone, depleted the major extracted monoaromatics. Genomic analyses revealed that EP4, GD01 and GD02 share an average nucleotide identity of 98% and that GD01 and GD02 harbor a predicted three-component carboxylase not present in EP4. A representative carboxylase gene was up-regulated ~100-fold during growth of GD02 on a mixture of the black liquor monoaromatics, consistent with the involvement of the enzyme in acetovanillone catabolism. More generally, quantitative RT-PCR indicated that GD02 catabolizes the black liquor compounds in a convergent manner via the β-ketoadipate pathway. Overall, these studies help define the catabolic capabilities of potential biocatalytic strains, describe new isolates able to catabolize the major monoaromatic components of black liquor, including acetovanillone, and facilitate the design of biocatalysts to valorize under-utilized components of industrial lignin streams.